(untitled) (Journal of Foreign Language Studies, 2025)
This study aims to develop a questionnaire on the use of self-regulated speaking L2 learning strategies based on Oxford’s (2011) Strategic Self-Regulation (S2R) Model. The study was conducted with 379 (78 male, 301 female) participants. In order to determine construct validity, Explanatory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were applied. Depending on the results of EFA, the scale is composed of 40 items on a 5-point Likert scale embedded in 6 dimensions (the total variance explained is 69.829%, factor loadings of 40 items vary from .922 to .691). CFA confirmed the results of EFA, and the findings showed that the model had acceptable fit (CMIN/df = 1.424, CFI = .971, GFI = .884, RMSEA =.033 and TLI = .969). The overall reliability of the model demonstrated that the model is acceptable with a Cronbach’s alpha of 0.82. The results show that the scale is a viable and reliable tool that can be used to determine which speaking strategies L2 learners prefer to use and how much they apply those strategies in the English language learning environment.